Reconstruction of Financial Crime Investigation Methods in Law Enforcement in The Era of the Industrial Revolution 4.0 - Sukardi Sukardi (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the construction of the concept and method of financial crime investigation in the Netherlands in the law enforcement system in Indonesia to deal with financial crime in the era of the industrial revolution 4.0. The method used is normative research because it only uses secondary data in the form of primary, secondary and tertiary legal materials with conclusions drawn using deductive reasoning methods. The urgency of this research is because the development of crime that is not symmetrical with its legal efforts in the era of the industrial revolution 4.0, has an impact on efforts to enforce the rule of law which will affect reciprocally with the democratic process in Indonesia. The novelty of the research is an investigative method that combines civil and criminal concepts and economic accounting concepts with criminal law concepts. The results of the study are the strategy for law enforcement of financial crimes and financial technology in the era of the industrial revolution 4.0, by building a legal system, namely on the substance of the law, regulatory changes are built that are oriented towards proving the profits from crime through the concept of follow the money. In the aspect of legal structure, build a synergistic and harmonious coordination system between law enforcers and between institutional and private departments with an online networking system. In the aspect of legal culture, building a database system through a data bank, building a business economic infrastructure with a digital transaction system.